2021
DOI: 10.1021/acssensors.1c00358
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Heterogeneity of Small Extracellular Vesicle Populations in Multiple Cancer Types via an Ultrasensitive Chip

Abstract: Identifying small extracellular vesicle (sEV) subpopulations based on their different molecular signatures could potentially reveal the functional roles in physiology and pathology. However, it is a challenge to achieve this aim due to the nanosized dimensions of sEVs, low quantities of biological cargo each sEV carries, and our incomplete knowledge of identifying features capable of separating heterogeneous sEV subpopulations. Here, a sensitive, multiplexed, and nano-mixing-enhanced sEV subpopulation characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The recently developed high throughput small EV subpopulation characterization platform (ESCP) demonstrated successful multiplex phenotypic detection of EV-related biomarkers utilizing nanoscopic flow and barcoding for multiplexed detection. 145 Their results emphasize the implication of EV subpopulation isolation for investigating the illusive pathology of tumor cells and immunomodulation capabilities.…”
Section: Ev Isolation and Characterization Technologiesmentioning
confidence: 86%
“…The recently developed high throughput small EV subpopulation characterization platform (ESCP) demonstrated successful multiplex phenotypic detection of EV-related biomarkers utilizing nanoscopic flow and barcoding for multiplexed detection. 145 Their results emphasize the implication of EV subpopulation isolation for investigating the illusive pathology of tumor cells and immunomodulation capabilities.…”
Section: Ev Isolation and Characterization Technologiesmentioning
confidence: 86%
“…50 µL of cell culture supernatant sample and 20 µL SERS nanotags were sequentially added to each well of the microfluidic device. Following previously optimized conditions ( 22 ), alternating current was applied for sample incubation (i.e., frequency = 500 Hz, amplitude = 800 mV, incubation time = 45 min) and for labelling with SERS nanotags (500 Hz, 800 mV, 20min), respectively. The alternating current induced a nanoscopic fluid flow on the surface of the antibody-functionalized asymmetric gold electrodes to stimulate EVs capture and labelling.…”
Section: Methodsmentioning
confidence: 99%
“…A different study recently reported the use of SERS-based microfluidics to characterize small EV subpopulations. 76 A microarray device was developed with three integrated electrodes functionalized with anti-CD63, -CD9, and -CD81 antibodies to create tetraspanin specific "hot spots" (Fig. 8D).…”
Section: E Surface Enhanced Raman Scatteringmentioning
confidence: 99%